2021
DOI: 10.1101/2021.09.15.460558
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The ARF GAPs ELMOD1 and ELMOD3 act at the Golgi and Cilia to Regulate Ciliogenesis and Ciliary Protein Traffic

Abstract: ELMODs are a family of three mammalian paralogs that display GTPase activating protein (GAP) activity towards a uniquely broad array of ADP-ribosylation factor (ARF) family GTPases that includes ARF-like (ARL) proteins. ELMODs are ubiquitously expressed in mammalian tissues, highly conserved across eukaryotes, and ancient in origin, being present in the last eukaryotic common ancestor. We described functions of ELMOD2 in immortalized mouse embryonic fibroblasts (MEFs) in the regulation of cell division, microt… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 158 publications
(243 reference statements)
0
6
0
Order By: Relevance
“…In contrast, ELMOD family members are thought to act as ARF/ARL GAPs, with broad cellular effects, including on the actin cytoskeleton (Li et al, 2019b). All three vertebrate ELMOD proteins have recently been localized to basal bodies and linked to ciliogenesis, albeit with seemingly opposing effects: While loss of ELMOD1 and 3 reduced ciliation in mouse embryonic fibroblasts, loss of ELMOD2 actually resulted in an increase, with those cilia displaying abnormal morphology, including apparent splaying of axonemes and ciliary rootlet defects (Turn et al, 2021(Turn et al, , 2022; ultrastructural analysis has so far not been performed). Common to all three perturbations is a mislocalization of ciliary proteins, suggesting ciliary trafficking is at least partly responsible for the observed defects (Turn et al, 2021(Turn et al, , 2022.…”
Section: Mapk15 and Elmod As Highly Conserved Regulators Of Ciliogenesismentioning
confidence: 99%
“…In contrast, ELMOD family members are thought to act as ARF/ARL GAPs, with broad cellular effects, including on the actin cytoskeleton (Li et al, 2019b). All three vertebrate ELMOD proteins have recently been localized to basal bodies and linked to ciliogenesis, albeit with seemingly opposing effects: While loss of ELMOD1 and 3 reduced ciliation in mouse embryonic fibroblasts, loss of ELMOD2 actually resulted in an increase, with those cilia displaying abnormal morphology, including apparent splaying of axonemes and ciliary rootlet defects (Turn et al, 2021(Turn et al, , 2022; ultrastructural analysis has so far not been performed). Common to all three perturbations is a mislocalization of ciliary proteins, suggesting ciliary trafficking is at least partly responsible for the observed defects (Turn et al, 2021(Turn et al, , 2022.…”
Section: Mapk15 and Elmod As Highly Conserved Regulators Of Ciliogenesismentioning
confidence: 99%
“…Amongst those, we observed downregulation of Dcdc2 , encoding for a protein containing 2 doublecortin peptide domains, localizing to primary cilia and playing a role for tubulin binding, microtubule polymerization and Wnt signaling regulation (Schueler et al, 2015). We further found that several differentially downregulated genes encode for Golgi-associated proteins and proteins involved in vesicle trafficking, including Rab6b (Wanschers et al, 2007), the ARF GAP Elmod1 (Turn et al, 2021) which has very recently also linked to protein transport from the Golgi to the cilium (Turn et al, 2021), Myo5c (Sladewski et al, 2016) and Zdhhc14 (Sanders et al, 2020) ( Figure 5; G and H ). While GO term analysis did not reveal enrichment of G-protein-coupled receptor signaling, we detected upregulation of two G-protein signaling pathway associated genes Rgs2 and Snca .…”
Section: Resultsmentioning
confidence: 85%
“…In line with impaired Golgi protein transport functions under stress, we observed reduced expression of several other Golgi-associated proteins including Elmod1 in all dynein-2 mutants (both ciliated and non-ciliated cells) compared to controls. The GTPase activating protein ELMOD1 is a GTPAse activating protein which acts mainly on ADP-ribosylation factor (ARF) family GTPases and knock out affects primary cilia formation, reducing ciliary ARL13B expression and resulting in accumulation of INPP5E and IFT140 at the Golgi (Turn et al, 2021). Knockout mice present with fused and elongated stereocilia in the inner ear and disturbed intracellular vesicle trafficking in knockout cells has been described (Krey et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Amongst those, we observed downregulation of Dcdc2, encoding for a protein containing 2 doublecortin peptide domains, localizing to primary 13 cilia and playing a role in tubulin binding, microtubule polymerization and Wnt signaling regulation (Schueler et al, 2015). We further found that several differentially downregulated genes encode for Golgi-associated proteins and proteins involved in vesicle trafficking, including Rab6b (Wanschers et al, 2007), the ARF GAP Elmod1 (Turn et al, 2021) which has very recently also linked to protein transport from the Golgi to the cilium (Turn et al, 2021), Myo5c (Sladewski et al, 2016) and Zdhhc14 (Sanders et al, 2020) (Figure 5G and H). While GO term analyses did not reveal enrichment of G-protein-coupled receptor signaling, we detected upregulation of two Gprotein signaling pathway associated genes Rgs2 and Snca.…”
Section: Wdr34 and Wdr60 Human Disease Alleles Influence Gene Transcr...mentioning
confidence: 78%
“…In line with impaired Golgi protein transport functions under stress, we observed reduced expression of several other Golgi-associated proteins including ELMOD1 in all dynein-2 mutants (both ciliated and non-ciliated cells) compared to controls. The GTPase activating protein ELMOD1 is a GTPase activating protein that acts mainly on ADP-ribosylation factor (ARF) family GTPases and knockout affects primary cilia formation, reducing ciliary ARL13B expression and resulting in accumulation of INPP5E and IFT140 at the Golgi (Turn et al, 2021). Knockout mice present with fused and elongated stereocilia in the inner ear and disturbed intracellular vesicle trafficking in knockout cells has been described (Krey et al, 2018).…”
Section: Discussionmentioning
confidence: 99%